Acute toxicity related to misuse (nonmedical use) of tramadol: Experience of the European Drug Emergencies Network Plus. Issue 4 (15th July 2020) - Layne, Kerry A.; Dargan, Paul I.; Dines, Alison M.; Leaper, Craig; Yates, Christopher; Hovda, Knut Erik; Heyerdahl, Fridtjof; Archer, John R.H.; Giraudon, Isabelle; Wood, David M.; ,
Abstract : Following the development of the tramadol crisis currently affecting countries in the Middle East, and Africa, there has been increasing international interest in the regulation of tramadol. This study investigates the misuse of tramadol in patients presenting to emergency departments across Europe. Data from 32 emergency departments in 21 countries were extracted from the Euro‐DEN Plus database for the 4‐year period from 1 January 2014 to 31 December 2017. Of the reported 24, 957 emergency department presentations, tramadol misuse was reported in 105 (0.4% presentations). Tramadol misuse was most common in Bratislava (Slovakia; n = 11, 7.5% of all presentations to this centre), Riga (Latvia; n = 4, 4.9%) and Munich (Germany; n = 17, 2.9%). On arrival, 14 (13.3%) of presentations were in coma/Glasgow coma score ≤ 8 and 9 of these had a respiratory rate <12 breaths/min. These presentations potentially pose a significant burden on emergency departments with a large proportion requiring admission to hospital for ongoing care.